An unusual neurological complication in a patient with ulcerative colitis - Hayretdin Köklü; Evrim Kahramanoğlu Aksoy; Ömer Öztürk; Rahşan Göçmen; Seyfettin Köklü (Turkish Journal of Gastroenterology, 2019)
-